Innovation at the Bottom of the Pyramid - Amburle, Dipti (SFIMAR Research Review, 2016)
"The real source of market promise is not the wealthy few in the developing world, or even the emerging middle-income consumers: It is the billions of aspiring poor who are joining the market economy for the first time", C.K. Prahlad in his book "Fortune at the bottom of the pyramid". The question here arises is that of self sufficiency of these people at the base. When self sufficiency is the concern, the solution is always in the form of an innovation. Innovation in the form of a product invention or a strategy for improvisation or social benefit programs by corporates'. Possibilities of innovation can rise in the form of a company undertaking activities' for the up-liftment of tier 4 with a second aim to tap the fortune lying at the bottom of the pyramid and innovations that emerge directly from the people at this base with a concern to make their living better. Innovating at the bottom of the pyramid is nothing else than real.